Structure and orientation of an intermetallic phase in a W-Ni-Co alloy. Issue 10 (19th May 2019) - Sarkar, Rajdeep; Singh, Vajinder; Kumar, Suraj; Rao, Y. Venkateswara; Ghosal, P.; Nandy, T. K.
ABSTRACT: The aim of this investigation is crystal structure determination of an intermetallic phase formed in a W-Ni-Co alloy during a heat-treatment carried out at a temperature of 800°C. This intermetallic phase is expected to play a critical role on the final microstructure (fine tungsten particles in an FCC matrix that is present in between large tungsten grains) and thereby, on the properties of the alloy. 92W-5.3Ni-2.7Co alloy was prepared through powder metallurgy route (liquid phase sintering) followed by heat-treatment at 800°C for 5 h. The intermetallic phase formed at this temperature was characterised using transmission and scanning electron microscopes. The intermetallic phase was found to have orthorhombic crystal structure with Pnam (62) space group as determined using automated diffraction tomography along with precession electron diffraction. Chemical analysis in TEM suggested that the intermetallic phase is based on stoichiometry (Co, Ni)2 W. Orientation imaging of the phase was also carried out in TEM and EBSD to understand its evolution. Equiaxed or lath morphology of the intermetallic phase was found to depend on the crystallographic orientation relationship of the phase with the tungsten grains and the matrix phase.